ChemInform Abstract: Highly Enantioselective Synthesis of 1, 2, 3‐Substituted Cyclopropanes by Using α‐Iodo‐ and α‐Chloromethylzinc Carbenoids. Issue 14 (20th March 2013) - Beaulieu, Louis‐Philippe B.; Zimmer, Lucie E.; Gagnon, Alexandre; Charette, Andre B.
Abstract Trans‐iodocyclopropylmethanols obtained with excellent enantioselectivities by the presented new asymmetric iodocyclopropanation are further converted into 1, 2, 3‐substituted cyclopropanes either by reaction with electrophiles (X) or Negishi coupling with aryl iodides (XII).